Patient-Specific Implant for Anatomic Restoration of Lateral Femoral Condyle Contour After Impaction Fracture Associated With an Anterior Cruciate Ligament Tear - Marcin Mostowy, M.D.; Jakub Piękoś, M.Eng.; Wojciech Bocheński, M.S.; Przemysław A. Pękala, M.D., Ph.D.; Robert F. LaPrade, M.D., Ph.D.; Konrad Malinowski, M.D., Ph.D. (Arthroscopy Techniques)
Impaction fractures of lateral femoral condyle (LFC-IF) are challenging entities following anterior cruciate ligament tears. Anatomic reduction and restoration of the native LFC curvature is crucial in their treatment, because if they are neglected, it may potentially lead to incongruence in the lateral knee compartment with subsequent cartilage deterioration or damage to other intra-articular structures. Previously established operative techniques seem to achieve these milestones, yet there is still a potential risk of cartilage breakage or nonanatomical reduction. The presented technique addresses those weak points by the use of patient-specific implants, which provides the opportunity to closely restore the anatomical LFC curvature with minimal risk of osteochondral fracture of the LFC-IF site.